2011
DOI: 10.1128/jcm.05058-11
|View full text |Cite
|
Sign up to set email alerts
|

Septic Arthritis Due to Cellulosimicrobium cellulans

Abstract: Cellulosimicrobium cellulans has been reported as a rare cause of human pathogenesis. Infections mainly occur in immunocompromised patients and very often are associated with a foreign body. We report the first case of septic arthritis caused by C. cellulans in an immunocompetent patient. Our patient suffered a penetrating palm tree thorn injury to his left knee 8 weeks before admission. Although no foreign objects were found, they were suspected because previous reports suggest a frequent association with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Similar to a previous study (Magro-Checa et al, 2011), our sequencing results demonstrated that 16S rRNA sequencing alone may not be able to distinguish between the three closely related species, although the differentiation may not necessarily affect treatment (Brown et al, 2006). C. cellulans has been reported as being resistant to erythromycin and other macrolides but is considered susceptible to vancomycin, which was the therapy of choice in most of the reported cases.…”
Section: Case Reportsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar to a previous study (Magro-Checa et al, 2011), our sequencing results demonstrated that 16S rRNA sequencing alone may not be able to distinguish between the three closely related species, although the differentiation may not necessarily affect treatment (Brown et al, 2006). C. cellulans has been reported as being resistant to erythromycin and other macrolides but is considered susceptible to vancomycin, which was the therapy of choice in most of the reported cases.…”
Section: Case Reportsupporting
confidence: 75%
“…C. cellulans has been reported as being resistant to erythromycin and other macrolides but is considered susceptible to vancomycin, which was the therapy of choice in most of the reported cases. Other treatment options such as linezolid or rifampin may be associated with a higher rate of cure (Magro-Checa et al, 2011;Tucker et al, 2008).…”
Section: Case Reportmentioning
confidence: 99%
“…A characteristic feature of the members of this genus is cellulolytic activity. C. cellulans has been reported to be widely distributed in soil, clinical samples, and marine sponges . This organism has also been found to live in extreme environments of the Antarctic .…”
Section: Discussionmentioning
confidence: 99%
“…Bordetella holmesii, a well-described pathogen in asplenic and immunocompromised patients, has been reported rarely in immunocompetent patients [68]. Although Cellulosimicrobium cellulans usually causes infection in immunosuppressed patients, there has been a case report of this organism causing septic arthritis after a penetrating injury in an immunocompetent patient [69].…”
Section: Microbiologymentioning
confidence: 98%